(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background and Objective: Pulmonary tuberculosis(PTB) is a serious disease that mainly affects the lungs. The aim of this study was a Comparison between conventional, and molecular methods to diagnose M.tuberculosis complex (MTBC) and using serum TNF-? levels as a biomarker for evaluating the severity of the disease. Methodology: The study analyzed 586 sputa collected from suspected pulmonary tuberculosis patients (217 female and 369 male) their ages ranged from 16 to 66 years for mycobacteriological study, while the immuno-study included 85 blood samples that collected from eighty patients and five healthy persons (45 male,40 female) their ages (18-66) years. We tested all sputum samples by AFB direct stain and GX methods, while we cultured sputum restrictively for Patients who have two different outcomes by AFB direct stain and GX methods. TNF-? levels have been measured by sandwich ELISA in patients and healthy persons. Results: Our result showed detection of (135\586) patients infected with M.tuberculosis complex (MTBC) and (1\586) patient infected with non-mycobacterium tuberculosis(NMT) by AFB direct stain and GX methods comparing with culture method as a gold standard. Sensitivity and specificity for AFB direct stain and GX techniques for diagnosis PTB were (15.0% and 100% ) and (95.0% and 66.7% ) respectively. On the other side, TNF-? levels were elevated in inpatient groups compared with healthy persons. The mean of TNF-? levels measured in multidrug resistance tuberculosis (MDR-TB) patients was higher than in other cases. Conclusion: Our findings demonstrate that the sensitivity of the GX technique is higher compared to other techniques, and serum TNF-? levels can be used as a biomarker for evaluating the severity of pulmonary tuberculosis.